Diabetes mellitus and hyperhomocysteinemia - Kryvovyaz, Yu.O.; Vlasenko, M.V. (Ендокринологія | Endokrynologia, 2016)
The article presents a clinical case of diabetes in patients with hyperhomocystein-emia. Late diagnosis of hyperhomocysteinemia in this patient led to difculty in the  choice of the tactics of hypoglycemic therapy. Secondary diabetes in a patient was found to be positive using insulin analogues and taking into account carbohydrate and folate diet. A combination of both pathologies (diabetes mellitus and hyperhomocysteinemia) requires monitoring of carbohydrate disorders and permanent therapy  with vitamins B and folic acid.